The Power of International Collaboration in Advancing Haematology and Oncology: Fostering Excellence between the UK and Iraq. - Al-Hassani, Ahmed (Journal of the Faculty of Medicine Baghdad, 2025)
Modern international connectivity makes international cooperation essential for medical progress specifically in specialised medicine areas like haematology and oncology. Healthcare problems become more manageable when countries unite their expert knowledge with resources and creative solutions to achieve better patient results worldwide. The University of Baghdad should establish partnerships with UK healthcare organisations to address national healthcare deficiencies as they create mutual educational programs.The systematic collaboration between UK and Iraqi healthcare institutions shows potential to transform blood-related care services. This research illustrates that multidisciplinary teams (MDTs) as well as direct partnerships enable collaborative expert acquisition to boost patient care alongside innovation development. The UK healthcare sector can benefit from understanding how the Middle East integrates technology in healthcare services and delivers personalised care to patients